HUBUNGAN ANTARA KONSEP DIRI DENGAN KEMANTAPAN KEPUTUSAN KARIER MAHASISWA JURUSAN PENDIDIKAN LUAR SEKOLAH UNIVERSITAS NEGERI MEDAN - Nainggolan, Regina BM; Ginting, Rafael Lisinus (Jurnal Bimbingan dan Konseling Terapan, 2021)
This research is motivated by the problems of students who have a lot of problems about some students who do not have readiness, do not have knowledge, and have not received information about job opportunities in Non-Formal Education. This study aims to reveal the relationship between self-concept and the stability of career decisions. This research uses descriptive quantitative research with the correlation method. The subjects of this study were 75 people. The instrument used was a questionnaire and the scale used was a Likert scale. The research data were analyzed by simple regression. The results of this study indicate that there is a very positive relationship between self-concept and stability of career decisions.Keywords: Self Concept, Career Decisions, Career Stability, Stability of Career Decisions